On the Explicit Saturation Drain Current in the Generalized EKV Compact MOSFET Model - Garcia-Sanchez, Francisco J.; Ortiz-Conde, Adelmo (IEEE transactions on electron devices, 2021)
We present and discuss explicit closed-form expressions for the saturation drain current of short-channel metal-oxide-semiconductor field-effect transistors (MOSFETs) with gate oxide and interface-trapped charges, and including carrier velocity saturation, according to the generalized Enz-Krummenacher-Vittoz (EKV) MOSFET compact model. The normalized saturation drain current is derived as an explicit function of the normalized terminal voltages by solving the transcendental voltage versus charge equation using the Lambert W function. Because this special function is analytically differentiable, other important quantities, such as the transconductance and the transconductance-to-current ratio, can be readily expressed as explicit functions of the terminal voltages.